Drawing and documentation for the conservation: an interdisciplinary task - Carbonara, Giovanni (DISEGNARECON, 2012)
A good analysis of the historic built, founded on the graphic survey as his main instrument, will aim to promote an approach based on the interdisciplinary contribution of drawing and other research methodologies, physico-chemical, structural, archaeological and architectural properly. In the case of the conservation, then, will not miss the investigations on the degradation, possibly over extended periods of time in the form of a ’monitoring’. Common denominator will be an attitude of great attention to the ‘reality’ of the monument, i.e. to the concrete and actual materiality of the architecture